Sample path generation of the stochastic volatility CGMY process and its application to path-dependent option pricing - Young Shin Kim (Journal of Risk and Financial Management, 2021)
This paper proposes the sample path generation method for the stochastic volatility version of the CGMY process. We present the Monte-Carlo method for European and American option pricing with the sample path generation and calibrate model parameters to the American style S&P 100 index options market, using the least square regression method. Moreover, we discuss path-dependent options, such as Asian and Barrier options.
Keywords: C15; C22; C60; G13; 330; American option; barrier option; Lévy process; Monte-Carlo simulation; stochastic volatility